Lessons learned from the “spot the alien” citizen science campaign (2022–2025) in Maltese waters and the second record of Cephalopholis hemistiktos in the Mediterranean - Alan Deidun; Laura Prieto Gomez; Adam Gauci; Audrey Zammit; David Fernando Ramirez Montano; Maria Corsini-Foka; Bruno Zava; Alessio Marrone (Frontiers in Marine Science, 2026)
Introduction Citizen science is increasingly recognised as a valuable approach for monitoring marine non-indigenous species (NIS), range-expanding species (RES), and cryptogenic taxa. This study evaluates the outcomes of the Spot the Alien campaign in Maltese waters between 2022 and 2025. Methods A total of 441 expert-validated records of 30 NIS, RES and cryptogenic species were analysed to assess temporal and spatial reporting patterns, species richness, habitat and observation-method associations, reporting hotspots, and the influence of outreach activities. Results Reporting effort and species richness increased throughout the study, with 2025 yielding the highest number of records. Species accumulation and rarefaction analyses indicated that the campaign documented a substantial proportion of the detectable target fauna. Reporting patterns varied significantly among seasons, habitats, and observer groups, highlighting the influence of both ecological factors and reporting behaviour. The campaign also produced the second Mediterranean record of the Indo-Pacific grouper Cephalopholis hemistiktos. Discussion The Spot the Alien campaign demonstrates that expert-validated citizen science can provide reliable, cost-effective support for the surveillance of marine bioinvasions. The findings highlight the importance of sustained public engagement, rigorous validation, and long-term monitoring to improve early detection and inform future citizen-science initiatives.